Does artificial intelligence kill employment growth: the missing link of corporate AI posture - Bughin, Jacques (Frontiers in Artificial Intelligence, 2023)
An intense debate is on-going about how artificial intelligence (AI) technology investments have an impact on employment. The debate has often focused on the potential of AI for human task automation, omitting the strategic incentive for firm to cooperate with workers as to exploit AI technologies for the most relevant benefit of new product and service innovation. We calibrate an empirical model of how changes in employment relate to AI diffusion, based on a game-theoretical model of a firm exploiting the twin role of AI innovation and AI automation for both absolute and competitive advantage. Our estimation, based on a global survey of 3000 large companies across 10 countries, demonstrates that a firm employment growth both depends on two strategic postures,-that is, the firm relative maturity of AI adoption as well as its relative bias towards AI-based product innovation.